3D confocal microscope imaging of macromolecule uptake in the intact brachiocephalic artery. (October 2020) - Dazzi, Marta; Rowland, Ethan M.; Mohri, Zahra; Weinberg, Peter D.
Abstract: Background and aims: Elevated uptake of plasma macromolecules by the arterial wall is an early event in atherogenesis. Existing optical techniques for detecting macromolecular tracers in the wall have poor depth penetration and hence require en face imaging of flattened arterial segments . Imaging uptake in undistorted curved and branched vessels would be useful in understanding disease development. Methods: Depth penetration was increased by applying optical clearing techniques. The rat aorto-brachiocephalic junction was imaged intact by confocal microscopy after it had been exposed to circulating rhodamine-labelled albumin in vivo, fixed in situ, excised and then cleared with benzyl alcohol/benzyl benzoate. Tracer uptake was mapped onto a 3D surface mesh of the arterial geometry. Results: Tracer fluorescence was detectable throughout the wall closest to the objective lens and, despite a vessel diameter of c. 1 mm, in the wall on the other side of the artery, across the lumen. By tile scanning, tracer concentrations were mapped in the aorta, the brachiocephalic artery and their junction without opening or flattening either vessel. Optical clearing was also shown to be compatible with immunofluorescent staining and imaging of experimental atherosclerosis. Conclusions: The technique obviates the need for labour-intensive sample preparation associated with standard en face imaging. More importantly, it preserves arterial geometry, facilitating co-localisation of uptake maps with maps of biomechanical factors, which typically exist on 3D surface meshes. It will permit the correlation of haemodynamic wall shear stress with macromolecule permeability more accurately in regions of high curvature or branching, such as in the coronary arteries. Graphical abstract: Image 1 Highlights: Homogenising the refractive index of arterial tissue increases confocal imaging depth. Tracer uptake can be imaged in intact curved or branched segments. We demonstrate and validate the method at the rat aorto-brachiocephalic junction. The detected pattern of permeability is consistent with patterns of lesions and flow.